Cultured Meat – From Scientific Challenge to Consumer Acceptance as Sustainable Food Source - Lelia Voinea; Dorin Vicențiu Popescu; Teodor Mihai Negrea; Răzvan Dina (Amfiteatru Economic)
Cultured meat obtained in vitro from animal cells represents one of the recent concerns of specialists, who thus try to solve part of the issues related to animal welfare and sustainable meat production. Beyond the technical difficulties that must be overcome, the acceptance of cultured meat by consumers is not an easy goal to achieve, as it depends on factors acting both at the global and local levels. Since this paper focuses on Romanian consumers, the authors emphasize the importance of developing a general information framework that would allow first their understanding and further their acceptance of cultured meat. For this purpose, a systematic literature review, based on 34 articles, was carried out in order to observe good practices at international level, which led, in the past, to the acceptance of other significant innovations in the food field. Thus, five directions of action were identified: communication, knowledge, trust, perception, and attitudes. Based on these, a model of cultured meat acceptance by Romanian was developed. This initiative is unique in Romania so far and its results can be of interest for Romanian consumers and also for many categories of specialists, from scholars and researchers to practitioners interested in launching new products on the market or policymakers in the field of nutrition, public health, and agriculture. Further research is needed on the relationships between food security and safety, traditional meat production, and cultured meat as an alternative to real meat, before the marketplace launch of this new product